Posterior scleritis as an intraocular tumour. Issue 2 (February 1990) - Finger, P T; Perry, H D; Packer, S; Erdey, R A; Weisman, G D; Sibony, P A
Abstract : Posterior scleritis rarely presents as a large 'intraocular tumour' and continues to be a challenge in diagnosis and management. We present the case of a 66-year-old male with no known rheumatic disease, pain, proptosis, or diplopia, but with progressively decreasing visual acuity and a large, discrete 'subretinal tumour', 15 X 17 mm basal diameter and 8.3 mm apical height. Histologically the tumour was shown to be grossly thickened and necrotic sclera.